Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Persepsi Harga Terhadap Kepuasan Konsumen Pada Usaha Julietta Fried Chicken Di Bekasi Utara - Feby Lenny Ardiati; Dhian Tyas Untari; Andrian Andrian (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This study aims to determine the simultaneous influence between Service Quality, Product Quality, and Price Perception on Customer Satisfaction which has an impact on Julietta Fried Chicken's business in North Bekasi. The population in this study were all buyers at the Julietta Fried Chicken business in North Bekasi. This research method is quantitative research and to obtain samples in this study the authors used purposive sampling method and hair formula. Data collection through distributing questionnaires to 105 customers at the Julietta Fried Chicken business in North Bekasi. Data is processed using SPSS data analysis software version 26. This can be seen that the sig value is 0,002 <0,05 and the t-count value is 3,118> t-table 1,98326. The Product Quality variable has a positive and significant effect on Customer Satisfaction. It can be seen that the sig value is 0,000 <0,05 and the t-count value is 10,066> t-table 1,98326. The Price Perception variable has a positive and significant effect on Customer Satisfaction. This can be seen that the sig value is 0,024 <0.05 and the t-count value is 2,298> t-table 1,98326. From the research results obtained that partially and simultaneously the three independent variables are proven to be significant and have an effect on the Y variable. Therefore, the application of Service Quality, Product Quality, and Price Perception provided by the company can minimize the level of customer satisfaction at the Julietta Fried Chicken Business in North Bekasi.